Analisis Kualifikasi Pencurian Ringan dalam KUHP Baru (Undang-Undang Nomor 1 Tahun 2023) - Albi Ternando; Deddy Haryadi; Senta Jaya Sembiring; Sindi Feroliza; Emir Adzan Syazali (Wajah Hukum, 2026)
The reform of national criminal law through the enactment of Law Number 1 of 2023 concerning the Criminal Code is a strategic step taken by the state to adapt criminal law to the dynamics of social development and the values of justice that exist in society. One of the significant changes in the new Criminal Code is the re-arrangement of the qualifications for petty theft crimes, accompanied by the implementation of a more diverse and proportional sentencing system. This study aims to analyze the provisions of petty theft in the old Criminal Code and compare them with the new Criminal Code, as well as examine their application to the criminal system and law enforcement in Indonesia. The research method used is normative juridical legal research with a statutory regulatory approach and a conceptual approach. The research analysis is based on criminal law theory, the principle of legality, and criminal theory. The results show that the new Criminal Code provides a clearer classification of petty theft and emphasizes the use of alternative punishments, such as fines, community service, and supervision. The implementation of these provisions still encounters various obstacles, especially in terms of the readiness of law enforcement officers and public understanding of the concept of more humanistic and restorative punishment. Therefore, regulatory strengthening and ongoing outreach are necessary.